2018
DOI: 10.1515/jpem-2017-0406
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-seven mutations with three novel pathologenic variants causing biotinidase deficiency: a report of 203 patients from the southeastern part of Turkey

Abstract: We determined the mutation spectra of BD from the southeastern part of Turkey. The results of this study add three more mutations to the total number of mutations described as causing BD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
3
6
1
Order By: Relevance
“…Our genetic data confirmed that partial BD are more frequent than profound (88.1%) and are characterized by a distinctive genotype with a high prevalence of the c.1330G>C (p.Asp444His) variant (8,19). Essentially, all individuals with partial BD have the mutation c.1330G>C (p.Asp444His) in one or both alleles of the BTD gene in combination with a mutation associated with profound BD in heterozygosity, and this is in agreement with other studies already reported in the literature (10,14,16,21).…”
Section: Discussionsupporting
confidence: 91%
“…Our genetic data confirmed that partial BD are more frequent than profound (88.1%) and are characterized by a distinctive genotype with a high prevalence of the c.1330G>C (p.Asp444His) variant (8,19). Essentially, all individuals with partial BD have the mutation c.1330G>C (p.Asp444His) in one or both alleles of the BTD gene in combination with a mutation associated with profound BD in heterozygosity, and this is in agreement with other studies already reported in the literature (10,14,16,21).…”
Section: Discussionsupporting
confidence: 91%
“…In most previous studies, a higher frequency of profound and partial BTD forms was reported in the literature (5,20,21). The frequency of profound BTD determined based on the rst test results of this study was found to be similar to (8.2%) these previous reports.…”
Section: Discussionsupporting
confidence: 85%
“…This study reveals long-term follow-up consequences for patients diagnosed with BTD. Most of the reports related to BTD are crosssectional studies, and they involve the neonatal or early infant period (5,8,20). Most previous evaluations were performed with single measurement results, while the present study reports the long-term consequences of genotype-phenotype association with the change in consecutive biotinidase enzyme activity results.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…8 In an unpublished study conducted at our centre in newborns who were referred from the National Biotinidase Screening Program, the carrier incidence for BTD was determined to be 1:1155. Biochemical phenotypes are classified into two or four biochemical groups based on normal enzyme activity values 9,10 : profound (<10% of normal enzyme activity), partial (10.1%-30%), heterozygous (30.1%-66.5%) and normal (higher than 66.6%). It has been reported that the degree of multiple carboxylases and biotinidase enzyme activity are good indicators of the status of biotin deficiency.…”
Section: Introductionmentioning
confidence: 99%